Synthesis and characterization of anti-infective agents - Sharma, Monika; Sharma, Sonu; Arora, Neha; Sharma, Shreya; Matta, Yogesh; Sharma, Sharad (Journal of Applied Pharmaceutical Research, 2019)
Antifungal chemotherapy depends on bio-chemical alterations between fungi and mammals. Unlike bacteria, which are prokaryotes, both fungi and mammals are eukaryotes and the biochemical differences between them are not significant. However, there are some differences (in structure & metabolism) and focus is on these differences that act as targets for development of antifungal agents. The current recommendation of standard TB chemotherapy, called Directly observed treatment (DOTS) is a therapy of six month in which consists an first two-month phase of cure with four first-line drugs i.e. isoniazid, Rifampicin, Pyrazinamide, and Ethambutol. In this study large number of compounds is manufactured in which Most of the tested molecules showed maximum bacteriological growth inhibition at tested concentration. The combinations (7e, 7g, 7h, 7i and 7u) exhibited bacteriological growth inhibition at concentration of less than 40.0μg/ml against both microorganisms. Compounds (7o) showed growth of inhibition at 2.5μg/ml against both microorganisms. Additional challenging for all compounds at lower concentrations is mandatory to compare their activity through standard Streptomycin at its MIC to get exact MIC the manufactured combinations. Thus it can be concluded that designed 1, 3, 4-oxadiazole derivatives (7a-v) were manufactured successfully using planned synthetic outline. After manufactured the molecules were characterized using spectroscopy analysis and tested for the biological activity. All combinations showed anti-bacterial action at tested concentration against both gram positive and gram negative organisms and one of the compound 7o showed activity at concentration <2.5 μg/ml. Thus, these 1, 3, 4-oxadiazole results can then act as a potential principal for drug discovery of novel anti-infective agents.